Studies on the text of Caesar's Bellum civile - Damon, Cynthia 1957- (Oxford University Press, 2015)
'Studies on the Text of Caesar's Bellum Civile' is a companion volume to Damon's revised Oxford Classical Texts edition of Caesar's 'Bellum civile', his account of his civil war with Pompey. Comprising three parts, this volume investigates the detailed philological arguments that underpin the revised edition of the text
Published online: January 2017
Keywords: Caesar, Julius / De bello civili; Caesar, Gaius Iulius -- v100-v44 -- De bello civili; Textkritik